2015 IEEE Power &Amp; Energy Society Innovative Smart Grid Technologies Conference (ISGT) 2015
DOI: 10.1109/isgt.2015.7131802
|View full text |Cite
|
Sign up to set email alerts
|

The effects of flooding attacks on time-critical communications in the smart grid

Abstract: Many smart grid communications are delay sensitive and have very strict timing requirements for message deliveries. For example, trip protection messages must be delivered to the destination within 3 ms according to IEC 61850. Such timecritical communications are vulnerable to flooding attacks which attempt to increase message delivery delay through congesting the network channel and exhausting the computation resources of the communicating nodes. However, there is a lack of understanding on how much flooding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…If the security settings and the network design are inefficient all our intranet can be inoperable. To display the Li et al (2015) effects caused by this attack we will do it with the help of images, but to avoid making a collage of this, we will summarize the process into two parts: when the attack is generated and how to set the protection.…”
Section: Resultsmentioning
confidence: 99%
“…If the security settings and the network design are inefficient all our intranet can be inoperable. To display the Li et al (2015) effects caused by this attack we will do it with the help of images, but to avoid making a collage of this, we will summarize the process into two parts: when the attack is generated and how to set the protection.…”
Section: Resultsmentioning
confidence: 99%
“…Flooding attacks in IEC 61850 communication systems are extensively studied in [26] and [27]. They allow an attacker to inject false messages in the network, which could be real messages previously captured with the sole purpose of consuming communication or processing resources that could prevent legitimate messages from being delivered or processed on time.…”
Section: A High Level Vulnerabilitiesmentioning
confidence: 99%
“…This type of attack is referred to as flooding attack and it can result to not meeting the timing constraint for message delivery of IEC 61850 realtime protocols. The effects of flooding attacks on time-critical communications in IEC 61850 substation were studied in [25], [26]. Both papers concluded that the effects of flooding attacks are more severe in the wireless network than in the wired network.…”
Section: B Attacks Against Iec 61850mentioning
confidence: 99%